Differences in pharmacologic and demographic factors in male and female patients with vascular dementia, Alzheimer's disease, and mixed vascular dementia - Stanley, Madison; Poupore, Nicolas; Knisely, Krista; Miller, Alyssa; Imeh-Nathaniel, Adebobola; Roley, Laurie Theriot; Imeh-Nathaniel, Samuel; Goodwin, Rich; Nathaniel, Thomas I. (Frontiers in Dementia, 2023)
Background Increasing evidence suggests that demographic and pharmacologic factors may play a significant role in the epidemiology of dementia. Sex differences in prevalence also depend on dementia subtypes, such as Alzheimer's dementia (AD), vascular dementia (VaD), and mixed vascular-Alzheimer's dementia (MVAD). Therefore, studies are needed to investigate sex-specific differences, and identify potential therapeutic targets for both sexes. Methods Data was collected from the Prisma Health-Upstate Alzheimer's registry from 2016 to 2021 for 6,039 VaD patients, 9,290 AD patients, and 412 MVAD patients. A logistic regression was used to determine demographic and pharmacological factors associated with gender differences in patients with VaD, AD, and MVAD. Results In patients with VaD, African Americans (OR = 1.454, 95% CI, 1.257–1.682, p < 0.001) with increasing age (OR = 1.023, 95% CI, 1.017–1.029, p < 0.001), treated with aripiprazole (OR = 4.395, 95% CI, 2.880–6.707, p < 0.001), were associated with females, whereas patients treated with galantamine (OR = 0.228, 95% CI, 0.116–0.449, p < 0.001), memantine (OR = 0.662, 95% CI, 0.590–0.744, p < 0.001), with a history of tobacco (OR = 0.312, 95% CI, 0.278–0.349, p < 0.001), and ETOH (OR = 0.520, 95% CI, 0.452–0.598, p < 0.001) were associated with males. Among AD patients, African Americans (OR = 1.747, 95% CI, 1.486–2.053, p < 0.001), and Hispanics (OR = 3.668, 95% CI, 1.198–11.231, P = 0.023) treated with buspirone (OR = 1.541, 95% CI, 1.265–1.878, p < 0.001), and citalopram (OR = 1.790, 95% CI, 1.527–2.099, p < 0.001), were associated with females, whereas patients treated with memantine (OR = 0.882, 95% CI, 0.799–0.974, p = 0.013), and with a history of tobacco (OR = 0.247, 95% CI, 0.224–0.273, p < 0.001), and ETOH (OR = 0.627, 95% CI, 0.547–0.718, p < 0.001) were associated with male AD patients. In patients with MVAD, rivastigmine (OR = 3.293, 95% CI, 1.131–9.585, p = 0.029), memantine (OR = 2.816, 95% CI, 1.534–5.168, p < 0.001), and risperidone (OR = 10.515, 95% CI, 3.409–32.437, p < 0.001), were associated with females while patients with an increased length of stay (OR = 0.910, 95% CI, 0.828–1.000, p = 0.049), with a history of tobacco (OR = 0.148, 95% CI, 0.086–0.254, p < 0.001) and ETOH use (OR = 0.229, 95% CI, 0.110–0.477, p < 0.001) were more likely to be associated with males. Conclusions Our study revealed gender differences and similarities in the demographic and pharmacological factors of VaD, AD, and MVAD. Prospective studies are needed to determine the role of demographic and pharmacological factors in reducing sex-based disparities among VaD, AD, and MVAD patients.